Determination of static and dynamic forces for manufacture of corrugated belts for wind tunnel heat exchangers - Yu. V. Shchipkova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents the results of an experimental study aimed at determining the required load when rolling a corrugated heat exchanger belt for wind tunnels. The experiments are carried out on a horizontal milling machine model 6H81. The results of the experiment are applied to stainless steel tapes with a thickness of 0,3 to 0,4 mm.